2013
DOI: 10.1016/j.clinthera.2013.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Use of Complementary and Alternative Medicine Among Older Adults With Radiographic Knee Osteoarthritis

Abstract: Background Osteoarthritis (OA) accounts for more mobility issues in older adults than any other disease. OA is a chronic and often painful disease for which there is no cure. Cross-sectional studies have shown that older adults frequently use complementary and alternative medicine (CAM) and arthritis is the most common reason for CAM use. While previous research has profiled the sociodemographic and clinical characteristics of CAM users, few have provided information on variation in CAM use over time and most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 50 publications
2
29
1
1
Order By: Relevance
“…Currently, goals of OA management include controlling pain, maintaining and improving the range of movement and stability of affected joints, and limiting functional impairment [20, 21]. Because of the association of severe adverse events with the use of NSAIDs, at least one third of the older adults use some form of complementary and alternative medicine (CAM) for pain [22, 23]. …”
Section: Introductionmentioning
confidence: 99%
“…Currently, goals of OA management include controlling pain, maintaining and improving the range of movement and stability of affected joints, and limiting functional impairment [20, 21]. Because of the association of severe adverse events with the use of NSAIDs, at least one third of the older adults use some form of complementary and alternative medicine (CAM) for pain [22, 23]. …”
Section: Introductionmentioning
confidence: 99%
“…Rispler, Sara, Davenport, Mills, & Iskra, 2011; D. T. Rispler & Sara, 2011; Yang, Dubé, Eaton, McAlindon, & Lapane, 2013). Guided imagery (GI), the generation of positive sensory and affective images to promote therapeutic outcomes (Nelson et al, 2013), is a complementary approach for persons with osteoarthritis (Fouladbakhsh, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the UK, the National Institute for Health and Care Excellence (NICE) recommend the integration of manual therapy, but not acupuncture, in their OA management guidelines (National Institute for Health and Care Excellence, ), whereas acupuncture is recommended management in the US (National Institute of Arthritis and Musculoskeletal and Skin Diseases, ). In line with such inconsistency, a longitudinal study of 1121 older adults with knee OA found that about one‐third used at least one or more complementary medicines or therapies (CMTs) to manage their OA, but that such use was to some degree inconsistent with treatment guidelines (Yang, Dubé, Eaton, McAlindon, & Lapane, ). A recent US population‐based study similarly found that more than one‐third of adults with arthritis sought complementary care to manage their health, concluding that dialogues that foster open and nonjudgmental communication and sharing between conventional and complementary healthcare providers and patients should be encouraged, to facilitate best possible patient care (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%